Ectopic expression of DNA methyltransferases DNMT3A2 and DNMT3L leads to aberrant hypermethylation and postnatal lethality in mice. Issue 6 (4th March 2019) - Sasaki, Keisuke; Hara, Satoshi; Yamakami, Reina; Sato, Yusuke; Hasegawa, Saki; Kono, Tomohiro; Morohaku, Kanako; Obata, Yayoi
Abstract: DNA methylation is generally known to inactivate gene expression. The DNA methyltransferases (DNMTs), DNMT3A and DNMT3B, catalyze somatic cell lineage‐specific DNA methylation, while DNMT3A and DNMT3L catalyze germ cell lineage‐specific DNA methylation. How such lineage‐ and gene‐specific DNA methylation patterns are created remains to be elucidated. To better understand the regulatory mechanisms underlying DNA methylation, we generated transgenic mice that constitutively expressed DNMT3A and DNMT3L, and analyzed DNA methylation, gene expression, and their subsequent impact on ontogeny. All transgenic mice were born normally but died within 20 weeks accompanied with cardiac hypertrophy. Several genes were repressed in the hearts of transgenic mice compared with those in wild‐type mice. CpG islands of these downregulated genes were highly methylated in the transgenic mice. This abnormal methylation occurred in the perinatal stage. Conversely, monoallelic DNA methylation at imprinted loci was faithfully maintained in all transgenic mice, except H19 . Thus, the loci preferred by DNMT3A and DNMT3L differ between somatic and germ cell lineages. Abstract : Transgenic mice that constitutively expressed DNA methyltransferase (DNMT) 3A2 and DNMT3L were born normally but died within 20 weeks accompanied with cardiac hypertrophy and abnormal DNA hypermethylation at CpG islands of several genes. Conversely, monoallelic DNA methylation at most imprinted loci was faithfully maintained in all transgenic mice, indicating that the loci preferred by DNMT3A2 and DNMT3L differ between somatic and germ cell lineages.